TEACHING LEARNERS WITH READING DIFFICULTIES IN AN INCLUSIVE SETUP IN ZIMBABWE: CHALLENGES AND SOLUTIONS - CHIMHENGA, Dr. SYLOD (IJRDO- Journal of Educational Research, 2017)
The inclusion of all learners within the regular classroom has brought about a plethora of challenges for teachers. The purpose of this study was to explore the challenges faced by mainstream primary school teachers when teaching learners with reading difficulties in an inclusive education setup in Zimbabwe. The study used a combination of qualitative and quantitative methods of research. The study entailed a survey though questionnaires for the purpose of gathering information on the challenges faced by mainstream primary school teachers when teaching learners with reading difficulties. The questionnaire was administered on the teachers teaching dyslexic children in an inclusive set up. Fifty primary school teachers participated in the study. Participants were purposively selected from a group of primary school teachers teaching in inclusive set up who were willing to participate in the study. This study concluded that learners need to have their needs met concurrently with their non-dyslexic peers in an inclusive setting. The participants highlighted that parents did show an uncaring attitude like not helping learners with their homework or coming to the schools to inquire how best to help their dyslexic children. This study recommends there is need to provide basic training of teachers on dyslexia to enable them to cope with differentiated education.